CSR AND BRANDING BASED ON ISLAMIC PERSPECTIVE: HABERMAS' CRITICAL THEORY - Sri Wahyuni; Lilik Purwanti (CV. Radja Publika, 2023)
The purpose of this research is to explore the concept of CSR branding from the perspective of Islam and through the communication theory of Habermas. CSR is understood as a form of corporate responsibility that involves social concern for the environment in order to strengthen its positive image in society. However, some companies distort the concept of CSR towards branding, which is considered by the majority of society as a manipulative act. In Habermas' communication theory, CSR is one form of communicating the social and environmental effects of a company's economic actions on certain groups in society as a whole. And from an Islamic perspective, CSR branding can be communicated effectively and is permissible as long as it does not violate Sharia principles such as honesty, transparency, and avoiding things that contradict Islamic values